Pyoderma gangrenosum-like ulceration as a presenting feature of pediatric granulomatosis with polyangiitis - Rotem Semo Oz; Oluwakemi Onajin; Liora Harel; Rotem Tal; Tomas Dallos; Adena Rosenblatt; Lukas Plank; Linda Wagner-Weiner (BMC, 2021)
Abstract Background Granulomatosis with polyangiitis (GPA) is an anti-neutrophilic cytoplasmic antibody-associated vasculitis affecting small to medium-sized vessels and involves most commonly the kidneys and the respiratory tract. Skin involvement can be seen in up to 50% of children with GPA and is the initial presenting symptom in 7.7%. Pyoderma gangrenosum (PG)-like ulcers are rarely described as a skin manifestation in GPA and very few cases have been reported previously in children. Case presentation We describe 3 new pediatric cases of GPA with PG-like ulcerations. The median age at first symptom was 15 years. Two patients had PG-like ulceration as their initial presentation; additional symptoms eventually led to the diagnosis of GPA 2-24 months later. In 1 case, proteinase 3 (PR3) was negative when first tested, but converted to positive when systemic symptoms emerged; in the other 2 cases PR3 was positive at presentation. All 3 patients had prominent facial lesions. None of the patients responded to treatment with antibiotics or medications commonly used to manage PG, including corticosteroids and cyclosporine. All patients had excellent responses to rituximab. An electronic database literature review was performed and 4 previously reported cases were identified. We assessed the clinical characteristics, serology, and response to treatment of the previously reported and our newly diagnosed cases. Conclusion PG-like ulceration is a rare presentation of pediatric GPA which may precede classic systemic GPA symptoms. The predominance of facial ulcer, granulomatous and neutrophilic inflammation on skin biopsy and lack of response to PG treatments are characteristic of GPA-associated PG-like ulcers. Our review suggests that treatment with rituximab may be needed to improve the skin lesions. Recognizing that PG-like ulcerations can occur in pediatric GPA may result in timely diagnosis, appropriate treatment and improved prognosis.